2015
DOI: 10.1002/ece3.1783
|View full text |Cite
|
Sign up to set email alerts
|

An atypical reproductive cycle in a common viviparous Asia Agamid Phrynocephalus vlangalii

Abstract: Viviparous lizards living in cold climate of high altitude often exhibit atypical reproductive cycles, in which mating and fertilization occur synchronously and annually with parturition occurring at the end of the year. Nevertheless, detailed case studies on atypical reproductive cycles are few. Using anatomical data combined with behavioral observations, we examined the reproductive cycle of a common Asian agamid, Phrynocephalus vlangalii, from a high‐elevation area in Sichuan, China. Male spermiation of P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Many life history traits of this species show large amounts of geographic variation. Courtship occurs in May, and parturition occurs between mid‐July and late August (Wu, Fu, Yue, & Qi, ). Females at low‐elevation sites give birth earlier than those at high‐elevation sites (Li et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many life history traits of this species show large amounts of geographic variation. Courtship occurs in May, and parturition occurs between mid‐July and late August (Wu, Fu, Yue, & Qi, ). Females at low‐elevation sites give birth earlier than those at high‐elevation sites (Li et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, if increased survivorship (~longevity) leads to a larger adult body size, adult lizards would survive longer and would be older in the high-elevation population than the low-elevation population. and parturition occurs between mid-July and late August (Wu, Fu, Yue, & Qi, 2015). Females at low-elevation sites give birth earlier than those at high-elevation sites (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…), Phrynocephalus (Wu et al. ), Anolis (Hernández‐Salinas and Ramírez‐Bautista ), and Sceloporus (Ouifero et al. ; Du et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lately studies on several lizard species, such as Zootaca vivipara (Roitberg et al 2013) and species of the genus Takydromus (Du et al 2005), Phrynocephalus (Wu et al 2015), Anolis (Hern andez-Salinas and Ram ırez-Bautista 2015), and Sceloporus (Ouifero et al 2007;Du et al 2014;Lozano et al 2015) have found variation on several reproductive traits. In this sense, oviparous species which have wide distribution are good models to asses the changes on diverses life history characteristics, and mainly in the extension on reproductive cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal reproductive cycles can be synchronous or asynchronous with the female reproductive cycle. In synchronous cycles spermatogenesis occurs simultaneously with vitellogenesis and is followed by testicular regression and a resting period (Crews & Gans 1992;Whittier & Tokarz 1992;Pudney 1995;Ibargüengoytía & Cussac 1999;Ibargüengoytía 2004;Villagrán-Santa Cruz et al 2009;Boretto et al 2012Boretto et al , 2014Wu et al 2015). In asynchronous cycles, male and female gametogenesis are not simultaneous and there is sperm storage in females and/ or males (Marion & Sexton 1971;Whittier & Tokarz 1992;Flemming 1993Flemming , 1994Swain & Jones 1994;van Wyk 1995;Jones & Swain 1996;Huang 1997;Murphy et al 2006).…”
Section: Introductionmentioning
confidence: 99%